Are 18 holes enough for Tiger Woods? - Oliver Gürtler (University of Bonn, Bonn Graduate School of Economics (BGSE), 2005)
This paper addresses the selection problem in promotion tournaments. I consider a situation with heterogeneous employees and ask whether an employer might be interested in repeating a promotion tournament. On the one hand, this yields a reduction in uncertainty over the employees` abilities. On the other hand, there are costs if a workplace stays vacant.
Keywords: M51; D82; 330; Promotion tournament; selection; heterogeneous employees; repetition